Event-Related Potential Assessment of Visual Perception Abnormality in Patients With Obstructive Sleep Apnea: A Preliminary Study - Yang, Chao; Wang, Changming; Chen, Xuanyu; Xiao, Bing; Fu, Na; Ren, Bo; Liu, Yi (Frontiers in Human Neuroscience, 2022)
This study investigated the effect of obstructive sleep apnea (OSA) on the neural mechanism of visual perception. A preliminary case-control study was conducted. Seventeen patients with moderate to severe OSA in the sleep center of Civil Aviation General Hospital and twenty healthy controls matched for age, sex and education were recruited. The participants accepted the perceptual contour integration task, compared the differences of behavioral indicators between the two groups, and compared the differences of EEG data between the two groups through ERP technology. The groups did not differ significantly in age and gender, but they differed significantly in BMI (OSA higher than healthy controls, p < 0.05). The groups were not statistically different in terms of sleep structure and total sleep time. AHI, sleep efficiency and minimal SaO2 value in the OSA group were significantly different from those of the control group. The results showed that the average reaction time of the OSA group was significantly longer than that of the healthy control group in the contour integration task. There was no significant difference in the accuracy rate. The results of EEG showed that the amplitudes of N100 of OSA group were significantly higher than those of the control group at O1, Oz and O2 electrodes. There was no significant difference in latency between the two groups. At FCz electrode, the amplitudes of N200 of OSA group were significantly higher than those of the control group. Therefore, we conclude that in the early stage of perceptual integration task, although the neural response activity of moderate and severe OSA patients was not accelerated, they need to call more psychological resources, activate more neurons in the contour global recognition processing stage, and the compensatory effect of frontal lobe appeared in the stage of visual perception.